INTERNATIONAL INFORMATION TECHNOLOGIES AND THEIR ROLE IN IMPROVING THE EFFICIENCY OF ORGANIZATION OF THE HOTEL AND RESTAURANT BUSINESS - Kaziuka, N.P.; Humeniuk, V.V.; Semyrga, L.I.; Bielan, O.V. (The actual problems of regional economy development, 2023)
The article examines the essence of international information systems and technologies in the hotel and restaurant sphere. The need to integrate software into the operation of hotel complexes and restaurants as a basis for the formation and strengthening of competitive advantages for business entities in the rapidly growing market of hotel and restaurant services is substantiated. The role and features of the use of individual tools of international information technologies and systems in the hotel and restaurant business are highlighted. Information and communication facilities, components and tools that enable the storage, access, monitoring, processing and transmission of information in digital form are described. The essence of international information technologies and systems, their components for the development of the hotel and restaurant sphere, is revealed; the place and role of information and software in the activities of enterprises of the hotel and restaurant industry is defined; the mechanism of the formation of competitive advantages of economic entities due to the effective implementation of the customer relationship management system in their activities was identified; recommendations on the use of advanced tools, means and methods of information systems and technologies in the work of enterprises in the hotel and restaurant sphere are presented. The specifics of the application of information technologies that allow optimizing the management of business processes in hotels and restaurants are characterized, such as: information technologies that allow optimizing managerial activities in hotels and restaurants (computer systems of centralized hotel management, internal service management systems that ensure service efficiency customers, technologies for notifying about the availability of rooms, information systems that ensure the processes of ordering dishes in restaurants); service information systems and technologies (CRM systems and global reservation systems); information systems and technologies used in Internet marketing. The most popular and downloaded programs in the hotel and restaurant industry in the world according to the results of 2022 are described. The most common trends in information systems and technologies in the hotel and restaurant business have been identified, including mobile technologies (mobile applications, chatbots, virtual queues, QR codes for menus), contactless payments, the Internet of Things, robots, and virtual tours. The use of information and communication technologies at temporary accommodation and catering enterprises in Ukraine is analyzed.